2011
DOI: 10.1159/000322633
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Recurrence of Depression as Predictors of Cardiovascular Prognosis in Depressed Acute Coronary Syndrome Patients: A Systematic Review

Abstract: <i>Background:</i> Depression after acute coronary syndrome (ACS) is associated with worse cardiac outcomes. This systematic review evaluated whether depressed ACS patients are at differential risk depending on the recurrence and timing of onset of depressive episodes. <i>Methods:</i> MEDLINE, EMBASE and PsycINFO were searched from inception to 11 April 2009. Additionally, reference lists and recent tables of contents of 34 selected journals were manually searched. Eligible studies eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 96 publications
0
31
0
1
Order By: Relevance
“…On the one hand, sleep disturbances are risk factors for the development and course of cardiovascular diseases [33], [35], [36] and mental disorders [1]. On the other hand, sleep disturbances may be directly related to mental disorders [1], psychological consequences of severe medical diseases [37] or their physiological correlates such as sympathetic overactivity in heart failure [38]. However, our study was not designed to elucidate the underlying mechanisms but to determine the size of the problem in a large representative sample of Germany.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, sleep disturbances are risk factors for the development and course of cardiovascular diseases [33], [35], [36] and mental disorders [1]. On the other hand, sleep disturbances may be directly related to mental disorders [1], psychological consequences of severe medical diseases [37] or their physiological correlates such as sympathetic overactivity in heart failure [38]. However, our study was not designed to elucidate the underlying mechanisms but to determine the size of the problem in a large representative sample of Germany.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any association with biological risk factors of CHD or its surrogates contradicts assumptions of a direct link of type D with CHD mediated by inflammation and endothelial dysfunction. This picture differs from depression [46,47,48,49,50]. While not entirely consistent, associations of depression with endothelial dysfunction [45], biomarkers of inflammation [51], coagulation [52,53] and myocardial stress [54] have repeatedly been described.…”
Section: Discussionmentioning
confidence: 99%
“…It is this criterion that is most commonly used in post-myocardial depression studies. Many studies have shown that depression as defined by a BDI ≥ 10 is related to increased cardiovascular risk, including death [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%